Persepsi Penggemar BlackPink dalam Mengkonsumsi Konten di YouTube - Devanty, Audy; Okta Wibowo, Tangguh; Ramadita, Aura; Butar-Butar, Christina Stefani; Marcha, Kitra Riji (Jurnal Komunikasi, Sains dan Teknologi, 2023)
This research discusses how BlackPink fans, called BLINK, as an audience of BlackPink YouTube content because this research is motivated by fans who have their own way of idolizing someone. This research uses a descriptive qualitative research approach using the case study method. The research data was obtained from in-depth interview techniques with four informants, where it was found out why fans love BlackPink content on YouTube and idolize them more than other idols. The conclusion of this study shows how fans interpret BlackPink YouTube content as BLINK likes BlackPink YouTube content because of interest in BlackPink itself, which in any content shared can be entertaining and used as a source for fans to learn more about BlackPink as a group and as individuals. Furthermore, the level of fanatical devotion can be observed through their frequent responses to BlackPink's YouTube content, such as commenting, liking, and sharing among fellow fans.